Evaluation and Follow-up of Internal Quality Control of Total Bilirubin Testing at RSIA “X” - Rahmawati A, Mina; Feisal Rinaldi, Sonny; Riyani, Ani; Kurnaeni, Nani (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: A decrease in the sigma value of laboratory test parameters requires a comprehensive evaluation to identify the causes of instability and establish improvement strategies through internal quality control. Method: The research method is a descriptive study involving analysis of the Quality Goal Index (QGI), information collection through interviews, identification of causal factors using the Root Cause Analysis (RCA) approach, and the development of corrective and preventive action lists. Result: The cause of the decrease in sigma values in total bilirubin testing was found to be the reconstitution process of control materials that were not dissolved in low light conditions, resulting in decreased stability and sigma values in total bilirubin testing. This was due to the relocation of the laboratory to a new room with many light sources. The corrective action to be taken is to improve and add SPO for the dilution of quality control materials, which must be done in low light conditions. The preventive action taken is to ensure that SPO is implemented properly, as a way to minimize light absorption by covering the control material storage with aluminum foil. Conclusion: The results indicate that the decrease in sigma in total bilirubin testing is due to light exposure. A comprehensive system improvement is necessary to prevent further decreases in sigma values in total bilirubin testing.